The magnetic and magnetoresistance properties of ultrathin magnetite films grown on MgO substrate - SHVETS, IGOR; MCEVOY, CIARAN; RAMOS, RAFAEL (AMERICAN INSTITUTE OF PHYSICS, 2006)
We report on the properties of ultrathin (2, 4, 6, and 8?nm) epitaxial films of magnetite, Fe3O4, grown on MgO (100). Atomic force microscopy image and V-I curves suggest that the films at this thickness are still continuous. The resistivity versus temperature results imply that the conductivity mechanism in all these films is similar. The resistivity of 4?nm thick film is much greater than that of 6 and 8?nm films. The films show ferrimagnetic instead of reported superparamagnetic behavior. The dead layer formed by Mg diffusion between MgO substrate and magnetite films and also the dead layer on the top uncapped film could be the possible reasons for the anomalous resistivity and magnetic properties of the ultrathin films. The effect of the ?dead layer? in the thinner film is relatively greater than the one in the thicker film and should lead to a lower magnetoresistance.
Journal of Applied Physics
PROCEEDINGS OF THE 50TH ANNUAL CONFERENCE ON MAGNETISM AND MAGNETIC MATERIALS
PUBLISHED
San Jose, California
Keywords: Atomic, molecular and chemical physics; magnetoresistance